Remarks on philosphizing in the context of natural premises and personal identity of a philosopher - Radzioch, Lech (Folia Philosophica, 2004)
The author makes an attempt at analyzing the selected aspects of contemporary philosophizing, which often depends on the pressure from mass culture and conventional standards of «professionalism». He emphasizes the negative influence of such a way of philosophizing, which ignores the need of a minimal spiritual preparation for such a task of both the creators, as well as receivers. Meanwhile, the vitality of philosophy is based on validity of discussed problems that bother the minds and hearts of men of contemporary era and the making aware of them is the starting point of trustworthy philosophizing. The author criticizes the abstract and specialized «philosophical assessments», which are absorbed in a purely external way and without any relation to the actual experience of a man. The meaning of the so-called natural premises of individual philosophizing was emphasized. A philosopher can take up the task of his philosophical «self-creation» and achieve a necessary minimum of the spiritual identity of a person that has something to say on the basis of those premises. The process of a subjective establishment of philosophy requires a great deal of independence of mind and will of a philosopher because he is a subject to many external risks, including the pressure of various types of ideological «relativistic» thinking, which negates both the identity [the nature] of the subject and the negation of the sense of the European philosophical tradition. A reflection on philosophy, realized in relation with the reality of man in its actual empirical form, appears to be the only effective remedy for the attempts of a «deconstructive» reducing it to a formal «servant» of numerous dubious social concepts and ideologies.